THE EFFECT OF JOURNAL WRITING TECHNIQUE AND STUDENTS’ ACHIEVEMENT MOTIVATION TOWARD WRITING ACHIEVEMENT OF THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT OF UNDIKSHA - Mettaningrum, Gustiana; Dantes, N.; ., SUARNAJAYA, (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract This study aims at investigating any significance difference between the writing achievement of students who were taught by using journal writing technique and those by conventional writing technique and investigating any interactional effect between the implementation of those techniques and the students? achievement motivation upon students? writing achievement. This research was a post-test only control group design which was conducted in the fourth semester students of English Education Department, Undiksha. The result shows that there is a significant difference between the writing achievement of the students taught by using journal writing technique and those by conventional writing technique, where the students taught by using journal writing technique shows better writing achievement than the students taught by using conventional writing technique. In addition, there is a significant interactional effect between the implementation of those techniques and the students? achievement motivation. Keywords: Journal writing technique, achievement motivation, writing achievement